Long-term willows phytoremediation treatment of soil contaminated by fly ash polycyclic aromatic hydrocarbons from straw combustion. (September 2020) - Košnář, Zdeněk; Mercl, Filip; Tlustoš, Pavel
Abstract: A three-year experiment was conducted to investigate willows of Salix × smithiana Willd. ( S. smithiana ) phytoremediation of soil contaminated by polycyclic aromatic hydrocarbons (PAHs) derived by fly ash from biomass combustion. The total removal of ash PAHs in phytoremediation treatment was 50.9% after three consecutive years while the ash PAHs were decreased in natural attenuated soil by 9.9% in the end of the experiment. The ash and spiked PAHs with low and medium molecular weight were susceptible to be removed in higher rates than high molecular weight PAHs. Lower bioconcentration factors of individual PAHs were observed in willow shoots than in roots. The estimated relative direct removal of PAHs by S. smithiana in phytoremediation was significantly lower than 1% suggesting that the contribution of S. smithiana to take up PAHs from soil was negligible and the degradation of PAHs occurred mainly in soil. Phytoremediation using S. smithiana could be seen as a feasible and environmentally friendly approach of arable soils impacted by a PAH contaminated biomass fly ash. Graphical abstract: Image 1 Highlights: Fly ash PAHs were removed by 50.9% after three years of soil phytoremediation. Spiked PAHs were prone to be removed from soil similarly as ash PAHs. Low and medium molecular weight PAHs were found in willows shoots. Uptake of PAHs by willow plants from soil was significantly lower than 1%. Abstract : Manuscript as the first one investigated the Salix × smithiana Willd. phytoremediation treatment of soil impacted by 16 US EPA polycyclic aromatic hydrocarbons (PAHs) present in fly ash of biomass incineration during three-year experiment.